Natural Language Interfaces with Fine-Grained User Interaction: A Case Study on Web APIs - Su, Yu; Awadallah, Ahmed; Wang, Miaosen; White, Ryen W. (Proceedings of the 41th Annual International ACM SIGIR Conference on Research and Development in Information Retrieval (SIGIR 2018), 2018)
The rapidly increasing ubiquity of computing puts a great demand on next-generation human-machine interfaces. Natural language interfaces, exemplified by virtual assistants like Apple Siri and Microsoft Cortana, are widely believed to be a promising direction. However, current natural language interfaces provide users with little help in case of incorrect interpretation of user commands. We hypothesize that the support of fine-grained user interaction can greatly improve the usability of natural language interfaces. In the specific setting of natural language interfaces to web APIs, we conduct a systematic study to verify our hypothesis. To facilitate this study, we propose a novel modular sequence-to-sequence model to create interactive natural language interfaces. By decomposing the complex prediction process of a typical sequence-to-sequence model into small, highly-specialized prediction units called modules, it becomes straightforward to explain the model prediction to the user, and solicit user feedback to correct possible prediction errors at a fine-grained level. We test our hypothesis by comparing an interactive natural language interface with its non-interactive version through both simulation and human subject experiments with real-world APIs. We show that with interactive natural language interfaces, users can achieve a higher success rate and a lower task completion time, which lead to greatly improved user satisfaction.